Comparing the Profile of Temperament and Character Dimensions in Patients with Major Depressive Disorder and Bipolar Mood Disorder with a Control Group - Hajirezaei, Shahram (Iran J Psychiatry, 2017)
Objective: This study was conducted to compare the profile of temperament and character dimensions in patients with major depressive disorder and bipolar mood disorder with a control group. Method: In this causal-comparative study, the population consisted of 2 clinical groups (major depressive disorder and bipolar mood disorder) and a non-clinical group. The sample was 193 individuals (77 patients with major depressive disorder, 86 patients with bipolar mood disorder, and 30 controls), with an age range of 18 to 65 years and the mean age of 40.1. They were selected from Roozbeh psychiatric hospital using available sampling method. Tools used in this research included Temperament and Character Inventory-140 and General Health Questionnaire-28. Collected data were analyzed by independent t test and one-way analysis of variance using Statistical Package for the Social Sciences-22 software. Results: The results revealed a significant difference among groups in dimensions of novelty seeking, harm avoidance, persistence, self-directedness, and cooperativeness (P <0.05). The results showed that the mean was different in males and females only in the novelty seeking dimension (P <0.05). Conclusion: In general, our results revealed that patients with major depressive disorder and bipolar mood disorder have different personality profiles in some dimensions of temperament and character compared with the control group.